(untitled) - Lehninger, Albert L. (New York, 2005)
New edition of what is often considered the single best text on biochemistry, focusing on communicating to students the fundamentals of biochemistry in a way that reflects the field as it is understood today. Major recent advances covered range from the draft sequence of the human genome to elucidation of the high-resolution structure of the ribosome.
Protein-ezyme học
Keywords: Biochemistry,Công nghệ sinh học